Some quality properties of turkish fermented sausages consumed in konya - Mustafa Atasever; Abdullah Keleş; Ahmet Güner; Gürkan Uçar (Eurasian Journal of Veterinary Sciences)
In this research, chemical and microbiological properties of 30 Turkish sausage samples collected from Konya markets were determined. At the result of microbiological analyzes, the average count oftotal microorganisms, Coliform groups, Staphylococcus-Micrococcus and yeast and mould were determined as 5.7x106, 7.4x103, 3.2x105 and 6.4x104 /g respectively. In the chemical analyses of the samples, the average values of moisture, fat, protein, ash and salt contents were found to be 29.49 %, 30.9 %, 22.73%, 4.33 % and 2.93 % respectively; pH and water activity (Aw) values were found to be 5.24 and 0.806. During the assesment of results, microbiological and chemical properties of the sausage samples were found to be low quality. According to the results, the sausages (33.33 % in mic-robiologically, 86.67 %in chemically) weren't in accordance with Food Regulation and Standards.